Transport of Excited Charge Carriers in Conjugated Polymers. (1st January 2016) - Jiang, De-Yao; Zhang, Yu-Song; Chen, Wei-Kang; Li, Sheng; George, Thomas F.
Abstract : In a bulk heterojunction polymer solar cell, an exciton is dissociates into charged carriers in the heterojunction, where the resulting charged carrier − a polaron − transports along the polymer chain of the acceptor. During the polaron's transport, the external light field re-excites the polaron, rapidly decreasing the velocity of the polaron and restraining its transport. In this article, it is revealed that photoexcitation is a key factor for the charged carrier transport in a polymer solar cell, which largely determines the velocity of the charged carrier transport.